2021
DOI: 10.1021/acs.jpcc.1c02477
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Groups Enhancing the Mechanism of Nitrogen Reduction Reaction Properties on Ru- or Fe-Supported Nb2C MXene

Abstract: To rationally design electrocatalysts with high promising performance is essential for the nitrogen reduction reaction (NRR). Using the first principle density functional theory and ab initio molecular dynamic calculations, we systematically explored the activity, selectivity, and thermodynamic stability of the single-atom or tetra-nuclear metal clusters of Fe and Ru supported on Nb 2 C MXene modified by oxygen (fluorine) functional groups, resulting in one excellent electrocatalyst (labeling as Ru/Nb 2 CO 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…For Ti 2 CT 2 , it had been widely reported that the functional groups prefer to be located on the top of M2 site . For Nb 2 CT 2 and Cr 2 CT 2 , the report about the position of functional groups is not uniform, which mainly debates on the functional group location on C site or M2 site by different opinions. , …”
Section: Resultsmentioning
confidence: 99%
“…For Ti 2 CT 2 , it had been widely reported that the functional groups prefer to be located on the top of M2 site . For Nb 2 CT 2 and Cr 2 CT 2 , the report about the position of functional groups is not uniform, which mainly debates on the functional group location on C site or M2 site by different opinions. , …”
Section: Resultsmentioning
confidence: 99%
“…Due to the numerous family members, it is very time-consuming and expensive to use the trial and error method to search suitable single-metal-atom dopant for various MA 2 Z 4 materials. Therefore, the discovery of ideal NORR electrocatalysts needs to be accelerated through DFT calculations. , …”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure b, the values of U L (NRR) – U L (HER) of the candidate catalysts are all greater than 0, indicating they all have excellent NRR selectivity, and for these three catalysts, the U L (HER) values are much higher than NRR, indicating that HER has not yet occurred when NRR occurs, which can effectively catalyze NRR, while inhibiting HER. Furthermore, we evaluated the FE of NRR according to the Boltzmann distribution (FE NRR ): normalF normalE normalN normalR normalR = 1 1 + normale normalΔ G / k normalB T × 100 % . , Where Δ G is the difference in PDS free energy between HER and NRR, namely, U L (NRR) – U L (HER), k B is the Boltzmann constant (8.617 × 10 –5 eV/K), and T is the temperature (298.15 K). The calculation results are shown in Table .…”
Section: Resultsmentioning
confidence: 99%